Susceptibility profile of clinical isolates of non-Cryptococcus neoformans/non-Cryptococcus gattii Cryptococcus species and literature review (2010)
ABSTRACT: The in vitro susceptibility profi le of 24 clinical isolates of non- Cryptococcus neoformans /non -Cryptococcus gattii Cryptococcus species was analysed. In addition, the susceptibility results of 98 other strains from seven different reports were reviewed. The latter included studies which used antifungal susceptibility testing reference procedures or commercial methods which exhibited high correlation rates with the reference procedures. A total of 122 isolates were analysed (57 Cryptococcus albidus , 39 Cryptococcus laurentii , ten Cryptococcus uniguttulatus , ten Cryptococcus humicola , four Cryptococcus curvatus , and two Cryptococcus luteolus ). Amphotericin B was in vitro the most active compound against all species, while fl ucytosine and candins were inactive. Fluconazole exhibited a limited in vitro activity, particularly against C. albidus , C. uniguttulatus and C. laurentii . Voriconazole, itraconazole and posaconazole were active against most of isolates, but we found signifi cant rates of decreased susceptibility. Identifi cation and susceptibility testing of Cryptococcus spp. should be performed on a routine basis in view of their unpredictable susceptibility profi les.